13 Testosterone Replacement Therapy: Patient Reported Preferences. Issue 1 (1st April 2022) - Loeb, C; Schneider, D; Nguyen, J; Yafi, F
ABSTRACT: Introduction: Hypogonadism is common in the aging man, though it is often underdiagnosed and undertreated. Men with symptomatic hypogonadism can be treated with testosterone replacement therapy (TRT) in a wide variety of methods, such as intramuscular, transdermal, subcutaneous, intranasal, and oral. A number of factors including cost, efficacy, adverse effects, and mechanism and frequency of administration, must be considered when prescribing TRT to promote maximum patient satisfaction and clinical results. Objective: This study seeks to determine the attitudes, opinions, and preferences of men regarding their testosterone replacement therapy and the factors that influence these preferences. Methods: An anonymous online survey was distributed via REDcap, an online data collection engine, to 783 men currently on TRT in a single men's health clinic. Men answered questions relating to demographics, comorbidities, and social history, as well as validated questionnaires: Sexual Health Inventory for Men (SHIM) for erectile dysfunction and Androgen Deficiency in the Aging Male (ADAM) for hypogonadism. They were also asked about prior and current method of TRT and overall satisfaction with their current regimen. Patient preferences regarding administration, cost, effectiveness, and adverse side effects were assessed both qualitatively and in head-to-head comparisons. Results: The average age of the 130 respondents was 64.3 years (32-87). The most commonly reported method of administration was injection (57.3%), followed by topical ointment (21.8%), under-the-skin auto-injector (9.7%), implantable pellet (7.3%), and swallowed pill (4.0%). Overall satisfaction with current therapy was reported as very satisfied (36.0%), somewhat satisfied (25.6%), neutral (22.4%), somewhat dissatisfied (8.8%), and very dissatisfied (7.2%). Submuscular injection was the most commonly preferred method of administration at 40.5%, followed by swallowed pill (32.5%), under-the-skin auto-injector (23.8%), topical ointment (23.0%), nasal spray (20.6%), implantable pellet (15.9%), and skin patch (10.3%). When asked about preferences regarding testosterone injection therapy, 66.4% preferred self-administration at home; only 17.6% of patients preferred longer lasting injections if they had to be administered in the clinic. Patients ranked the potential benefits of therapy from most to least important as: improved sexual function, increased muscle strength, increased libido, reduced fatigue, decreased fat mass, increased bone density, improvement in depression, reduced hair loss, improvement with other medical problems, and improvement in anemia. Patients ranked the potential side effects of therapy from most to least concerning as: heart problems, blood clots, liver problems, breast growth, difficulty urinating, testicular shrinkage, gastrointestinal irritation, acne, and skin irritation. In head-to-head comparisons, patients preferred an administration method with the most therapeutic efficacy, fewest side effects, most convenient administration, preferred method of administration, and preferred frequency of dosing over cost. Furthermore, patients preferred efficacy and fewer side effects to convenience, method, and frequency of dosing. Conclusions: The majority of respondents were overall satisfied with their current therapy. The preferred TRT option was self-injection therapy at home. Treatment efficacy and fewer side effects were the most important considerations for patients on TRT. Patient preferences should be a strong consideration for providers when prescribing testosterone replacement therapy. Disclosure: No